A Step towards Sustainable Society: The Awareness of Carbon Dioxide Emissions, Climate Change and Carbon Capture in Malaysia - Ghazali, Zulkipli; Zahid, Muhammad; Kee, Tan Siok; Ibrahim, M. Yussoff (International Journal of Economics and Financial Issues, 2016)
Public awareness is crucial to mitigate negative impacts on the environment. The aim of the study is to explore the level of public awareness in five states of Malaysia (Perak, Melaka, Johor, Pahang and Terengganu) regarding CO2 emissions, climate change and carbon capture and storage (CCS). A questionnaire floated for exploring public awareness regarding CO2 emissions, climate change and CCS. Based on the questionnaire data was collected from five states (Perak, Melaka, Johor, Pahang and Terengganu) of Malaysia. These states were chosen on the basis of high concentration of heavy industries and plants, including petrochemical, natural gas processing, electricity generating, and cement plants. The study found that the public awareness of CO2 emissions and climate change is high as compared to the level of awareness towards CCS, because some of the respondents have never/ not heard about CCS. Furthermore, the study revealed that the respondents have several misperceptions about CO2 emissions, climate change and CCS. Most of them only heard about CO2 emissions, climate change and CCS only through print, electronic and social media. This study investigated public awareness about CO2 emissions, climate change and CCS only in 5 states of Malaysia; however, in future the study could be extended and explored in all states of Malaysia. The findings offer significant implications for environmental policies and strategies in curbing the negative environmental impacts of CO2 emissions in Malaysia as a whole. Keywords: Public awareness, CO2 emission, Climate Change, Carbon Capture and Storage (CCS), Malaysia JEL Classifications: L13, Q32